APPLICATION METHODS GUIDED DISCOVERY IN THE EFFORT IMPROVING SKILLS OBSERVING STUDENT LEARNING IPA IN THE FOURTH GRADES IN PRIMARY SCHOOL - Septikasari, Zela (Universitas Ahmad Dahlan, 2015)
The purpose of this research was to improve improve the skills of observing in science learning by using guided discovery. This type of research is a collaborative classroom action research with teachers and research subjects Elementary School fourth grade students in SD Lempuyangan 1, Yogyakarta. The results showed that the percentace of students who has score B on pre- action of 23.53%; in the first cycle increased to 38.24%; and 91.18% in the second cycle. Thus in the first cycle an increase of 14.71%, 52.94% in the second cycle, and the accumulated increase of 67.65%. It shows that guided discovery method can improve the skills of observing students and enables students to find their own concepts of science so that learning will be more meaningful.